STUDI KOMPARATIF PENERIMAAN ZAKAT PELAYANAN SECARA OFFLINE DAN ONLINE DI BADAN AMIL ZAKAT NASIONAL (STUDI KASUS BAZNAS KOTA PONTIANAK) - Elvira, Nadia Olga; Supriaman, Supriaman; Bariyah, Nurul (Program Studi Ekonomi Syariah IAI Muhammadiyah Bima, 2024)
This research aims to analyze the mechanism of zakat collection through offline and online service systems so that the potential of zakat can be achieved. Based on data from the Central Bureau of Statistics (BPS), the number of Muslims in Pontianak City in 2019 was around 509,437 and increased to 511,431 people in 2020. The National Amil Zakat Agency stated that the potential for zakat in Pontianak City reached 200 billion per year, however, the realization of current zakat revenue is still far from that figure. This descriptive qualitative research with a literature review method, uses primary and secondary data. The analysis shows that both offline and online service systems are equally effective and significant in increasing zakat revenue at BAZNAS Pontianak City. However, compared to the offline system, zakat revenue in BAZNAS Pontianak City is higher after the implementation of the online zakat collection system.